2016
DOI: 10.1371/journal.pone.0167469
|View full text |Cite
|
Sign up to set email alerts
|

An Insecticide Further Enhances Experience-Dependent Increased Behavioural Responses to Sex Pheromone in a Pest Insect

Abstract: Neonicotinoid insecticides are widely used to protect plants against pest insects, and insecticide residues remaining in the environment affect both target and non-target organisms. Whereas low doses of neonicotinoids have been shown to disturb the behaviour of pollinating insects, recent studies have revealed that a low dose of the neonicotinoid clothianidin can improve behavioural and neuronal sex pheromone responses in a pest insect, the male moth Agrotis ipsilon, and thus potentially improve reproduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, we cannot conclude whether this large range of effects is due to a direct effect of clothianidin, or of its bio-transformed metabolites, or of a general response due to the stress induced by the insecticide exposure (i.e., oxidative stress, increase in metabolic cost…). Nevertheless, these neuronal changes could provide an explanatory element for the behavioral and neuronal sensitivity modifications that we observed previously in clothianidin-treated males [ 17 , 23 , 88 ].…”
Section: Discussionmentioning
confidence: 78%
“…However, we cannot conclude whether this large range of effects is due to a direct effect of clothianidin, or of its bio-transformed metabolites, or of a general response due to the stress induced by the insecticide exposure (i.e., oxidative stress, increase in metabolic cost…). Nevertheless, these neuronal changes could provide an explanatory element for the behavioral and neuronal sensitivity modifications that we observed previously in clothianidin-treated males [ 17 , 23 , 88 ].…”
Section: Discussionmentioning
confidence: 78%
“…A few notable exceptions have nonetheless been reported: in the pest moth Agrotis ipsilon, it was shown that a neonicotinoid insecticide enhanced the response to sex pheromones (Rabhi et al, ). Interestingly, an experience‐dependent response was also detected with re‐exposure leading to increased effect on pheromone sensitivity as measured through male orientation response assay (Abrieux et al, ). A similar impact on male reproductive behaviour was found for imidacloprid where a sublethal exposure of the neotropical brown stink bug Euschistus heros increased male reproductive fitness (Haddi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…G, olfactory glomerulus; KC, Kenyon cell; LN, local interneuron; OSN, olfactory sensory neurons; MBON, mushroom body output neuron; PN, projection neuron another insecticide, deltamethrin, a widely used pyrethroid (Lalouette et al 2016). So far, it is, however, not known if the observed modulatory effects of insecticides are caused directly by receptor-ligand interactions, or if insecticides cause modifications of neuromodulator levels or expression of their receptors (Abrieux et al 2013(Abrieux et al , 2014(Abrieux et al , 2016. In addition, pyrethroid insecticides were shown to disturb the wiring of olfactory glomeruli during postembryonic metamorphic development in M. sexta (Wegerhoff et al 2001).…”
Section: Abiotic Environmental Factorsmentioning
confidence: 99%